Evaluation of secondary and micronutrients for soybean and wheat production - Widmar, Aaron (Kansas State University, 2013)
The application of micronutrients to increase yields has become more popular with increased commodity prices and higher yielding crops. Two studies were completed evaluating secondary and micronutrient for soybean (Glycine max [L.] Merr.) and wheat (Triticum aestivum).The objective of the first study was to evaluate the response of soybean, under a double crop system after wheat, to soil-and foliar-applied macro and micronutrients. Macronutrients (N, P, K) were applied at 22 kg ha[superscript]-[superscript]1, micronutrients (Fe, Mn, Zn) were soil applied at 11 kg ha[superscript]-[superscript]1and S was applied at 22 kg ha[superscript]-[superscript]1. Plant response parameters were evaluated including changes in nutrient concentration, and seed yield response. Tissue samples were collected at the respective R1 growth stage. Samples were analyzed for the nutrients applied with the fertilizer treatments. Soybean seed yield slightly responded to soil-applied S, Mn, and Zn. When micronutrients were foliar-applied, seed yield was significantly decreased. The second study evaluated the application of S and micronutrients to winter wheat. The objectives were to evaluate the wheat response to sulfur and micronutrient fertilization and evaluate soil testing and tissue analysis as diagnostic tools. Fertilizer treatments consisted of sulfur, iron, manganese, zinc, boron, copper. All of the micronutrients were sulfate-based products and the sulfur treatments were applied as gypsum. Fertilizer treatments were applied as topdress in early spring. Soil samples were collected before fertilizer application and after harvest. Flag leaf samples were collected and analyzed for the nutrients applied with the fertilizer treatments. Significant increases in tissue concentration were observed when Zn, B, and S were applied. Significant increases in soil test Zn, Cu, B, and S were observed compared to the control treatment. Despite the increases in soil test concentration across locations, no significant increases in yield by any of the nutrients or combination of nutrients were observed.
Keywords: Double-crop soybean; Micronutrient fertilizer; Agronomy (0285)